Concept and Functional Structure of a Service Robot. (4th February 2015) - Pineda, Luis A.; Rodríguez, Arturo; Fuentes, Gibran; Rascon, Caleb; Meza, Ivan V.
In this paper, we present a concept of service robot and a framework for its functional specification and implementation. The present discussion is grounded in Newell's system levels hierarchy which suggests organizing robotics research in three different layers, corresponding to Marr's computational, algorithmic and implementation levels, as follows: (1) the service robot proper, which is the subject of the present paper, (2) perception and action algorithms, and (3) the systems programming level. The concept of a service robot is articulated in practice through the introduction of a conceptual model for particular service robots; this consists of the specification of a set of basic robotic behaviours and a number of mechanisms for assembling such behaviours during the execution of complex tasks. The model involves an explicit representation of the task structure, allowing for deliberative reasoning and task management. The model also permits distinguishing between a robot's competence and performance, along the lines of Chomsky's corresponding distinction. We illustrate how this model can be realized in practice with two composition modes that we call static and dynamic; these are illustrated with the Restaurant Test and the General Purpose Service Robot Test of the RoboCup@Home competition, respectively. The present framework and methodology has been implemented in the robot Golem-II+, which is also described. The paper is concluded with an overall reflection upon the present concept of a service robot and its associated functional specifications, and the potential impact of such a conceptual model in the study, development and application of service robots in general.